Correlation of the Thanetian-Ilerdian turnover of larger foraminifera and the Initial Eocene thermal maximum (IETM) confirming evidence from the Campo area (Pyrenees, Spain) - Pujalte, Victoriano; Schmitz, B.; Baceta, J. I.; Bernaola, G.; Dinarès-Turell, J.; Orue-Etxebarria, X.; Payros, A. (Anuário do Instituto de Geociências, 2006)
Abstract